We'll always have the movies : American cinema during World War II - McLaughlin, Robert L., 1957-2022; Parry, Sally E. (Book collections on Project MUSE., 2006)
During the highly charged years of World War II, movies perhaps best communicated to Americans who they were and why they were fighting. These films were more than just an explanation of historical events: they asked audiences to consider the Nazi threat, they put a face on both our enemies and allies, and they explored changing wartime gender roles. We'll Always Have the Movies shows how film after film repeated the narratives, character types, and rhetoric that made the war and each American's role in it comprehensible. Robert L. McLaughlin and Sally E. Parry have watched more than six-hundr.